Simulation of the local electric field in tetragonal phase of BaTiO₃ - Yatsenko, A.A.; Yatsenko, A.V. (Functional Materials, 2004)
The region of possible combinations of electronic dipole polarizability and effective charges of ions in BaTiO₃ structure at T = 293 К is established. It is shown that electronic polarizability of apical О²⁻ ion is anisotropic. The results obtained can be used for the computer simulations of BaTiO₃ structure peculiarities.